Breastfeeding and postpartum depression mechanisms and care - Janiszewska, Michalina; Sobkowiak, Maciej; Sobkowiak, Paulina; Jusiak, Justyna; Łuczak, Janusz; Dżumaga, Justyna; Łuczak, Jeremi; Łazik, Maria; Dybowska, Roksana; Walaszek, Marta (Journal of Education, Health and Sport, 2026)
Objective: To synthesize evidence on the association between breastfeeding and postpartum depression, emphasizing bidirectionality, proposed mechanisms, key modifiers (self-efficacy, stress and social support), and integrated intervention strategies. Methods: Narrative review of the peer-reviewed literature provided by the author, prioritizing meta-analyses, systematic reviews, randomized trials, and large observational or qualitative studies. Results: Across settings, postpartum depressive symptoms are associated with reduced breastfeeding initiation, exclusivity, and duration. Early cessation and negative breastfeeding experiences are also associated with higher depressive symptom burden in some populations. Self-efficacy and social support consistently correlate with both mood and feeding outcomes, and stress appears to amplify risk. Interventions spanning pregnancy through the postpartum period and combining lactation support with psychosocial care show the most consistent promise. Conclusions: Because breastfeeding and postpartum depression influence one another and share modifiable determinants, clinical pathways should integrate screening, individualized feeding support, and stepped mental health care.